1992
DOI: 10.1002/eqe.4290211004
|View full text |Cite
|
Sign up to set email alerts
|

Seismic analysis of the fatih sultan mehmet (second Bosporus) suspension bridge

Abstract: SUMMARYTheoretical dynamic characteristics of the Fatih Bridge in terms of natural frequencies and mode shapes of free vibration were obtained using a range of finite element models. Based on this free-vibration data, separate analyses of the asynchronous response of the bridge to earthquake excitation in three orthogonal axes with different speeds of wave propagation, and of stochastic response to vertical excitation were used to estimate levels of dynamic response due to seismic loading.Fatih is the third of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 15 publications
3
21
0
1
Order By: Relevance
“…Then, from the analysis of the data-set collected, it is shown that the WSUs provide robust and reliable estimates concerning the main modal properties of the bridge, and that these latter are in remarkable agreement with the results of Brownjohn et al (1992), and Erdik and Apaydin (2005).…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Then, from the analysis of the data-set collected, it is shown that the WSUs provide robust and reliable estimates concerning the main modal properties of the bridge, and that these latter are in remarkable agreement with the results of Brownjohn et al (1992), and Erdik and Apaydin (2005).…”
Section: Introductionsupporting
confidence: 67%
“…Previous works (e.g., Petrovski et al 1974;Tezcan et al 1975;Abdel-Ghaffar and Housner 1978;Brownjohn et al 1987;Erdik and Uckan 1988) showed that full-scale dynamic testing of suspension bridge by ambient vibration recording represent a reliable approach for the assessment of the free vibration characteristics (i.e., vibration mode shapes, frequencies and the associated damping ratios), the calibration of the analytical and finite element models, and the detection of changes in these vibration characteristics. Similar ambient vibration tests were conducted on the Fatih Sultan Mehmet Bridge (e.g., Brownjohn et al 1990Brownjohn et al , 1992Apaydin and Erdik 2001;Apaydin 2002;Kaya and Harmandar 2004;Erdik and Apaydin 2005). In particular, Brownjohn et al (1992) outlined, doing a direct comparison with theoretical results provided by Dumanoglu et al (1992), the importance of the experimental confirmation of such mathematical modeling.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…One purpose of the comparison is so that the finite element (FE) models can be used to predict performance during unusual loads such as earthquakes (Brownjohn et al 1992 andDumanoglu et al 1991). Even if resulting response is large enough that material and geometric nonlinearities become significant, the starting point for non-linear analysis would be a realistic linear model.…”
Section: Introductionmentioning
confidence: 99%
“…The original ambient vibration study (Brownjohn et al 1987) and the 1990/1991 extended monitoring (Brownjohn et al 1994) served the purpose of validating simulation software to be used for analysis and design of other bridges. Specifically, the finite element analysis procedure validated in the 1985 test was used for studying seismic response of the two Bosporus crossings (Dumanoglu et al 1992;Dumanoglu and Severn 1987), while the 1990/1991 study validated procedures for simulating the in-wind performance of the proposed Messina Straits Bridge (Diana et al 2003). …”
Section: Previous Measurement Campaignsmentioning
confidence: 99%